1996
DOI: 10.1074/jbc.271.30.17961
|View full text |Cite
|
Sign up to set email alerts
|

A New Syntaxin Family Member Implicated in Targeting of Intracellular Transport Vesicles

Abstract: Despite the central role vesicular trafficking occupies in protein targeting, the molecular coding of the trafficking signals and the mechanism of vesicle docking and fusion are just beginning to be understood. We report here the cloning and initial characterization of a new member of the syntaxin family of vesicular transport receptors. Syntaxin 6 is a 255-amino acid protein with two domains predicted to form coiled-coils, as well as a carboxyl-terminal membrane anchor. Syntaxin 6 is broadly expressed and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
137
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(143 citation statements)
references
References 31 publications
5
137
0
1
Order By: Relevance
“…those of other gene products in the database revealed that OSM1/SYP61 shares greatest sequence similarities with t-SNARE-type syntaxins from mammals ( Figure 12B) (Jahn and Südhof, 1999;Sanderfoot et al, 2000). The OSM1/SYP61 sequence also predicts structural characteristics similar to those of the syntaxin family of vesicle transport proteins (Bock et al, 1996;Sanderfoot et al, 2000). It has a predicted transmembrane domain (outside to inside helix, from amino acids 225 to 243; 85% probability) at the C-terminal end.…”
Section: Osm1/syp61 Encodes a Syntaxin Proteinmentioning
confidence: 92%
“…those of other gene products in the database revealed that OSM1/SYP61 shares greatest sequence similarities with t-SNARE-type syntaxins from mammals ( Figure 12B) (Jahn and Südhof, 1999;Sanderfoot et al, 2000). The OSM1/SYP61 sequence also predicts structural characteristics similar to those of the syntaxin family of vesicle transport proteins (Bock et al, 1996;Sanderfoot et al, 2000). It has a predicted transmembrane domain (outside to inside helix, from amino acids 225 to 243; 85% probability) at the C-terminal end.…”
Section: Osm1/syp61 Encodes a Syntaxin Proteinmentioning
confidence: 92%
“…Syntaxin 6 contains an N-terminal domain followed by a SNARE motif and a single C-terminal membrane anchor. This primary structure organization, as well as significant homology to several syntaxin family members in the SNARE motif, led to the classification of this protein as a syntaxin family member (9). Moreover, syntaxin 6 coprecipitates with vps45, a sec1-like protein (8).…”
mentioning
confidence: 99%
“…Syntaxin 6 also shares significant sequence homology with the C-terminal SNARE region of SNAP-25 (9). A recent genomescale comparison of SNARE-motif sequences, coupled with the constraint that the four SNARE families be roughly equal in size, placed the syntaxin 6 SNARE motif in the S25C family rather than the syntaxin family (5).…”
mentioning
confidence: 99%
“…Its localization to the plasma membrane and its interaction with the synaptic vesicle v-SNARE synaptobrevin point to its function as a t-SNARE. Subsequently, a family of syntaxin-related molecules that shares 23-84% amino acid identity has been identified (6,9). These syntaxins are more ubiquitous in their expressions in various tissues, which is indicative of their possible functions in other vesicular transport steps in the cell.…”
mentioning
confidence: 99%
“…These syntaxins also display a variety of cellular localizations within the secretory pathway. Whereas syntaxins 2, 3, and 4 are apparently cell surface proteins (6, 10 -11), syntaxin 5 and syntaxin 6 are localized to the Golgi region (6,9).…”
mentioning
confidence: 99%